EVALUASI PROGRAM PELATIHAN DAN PENDAMPINGAN BAHAN AJAR BAGI GURU-GURU SMAN 5 KEDIRI - Sopiah Sopiah,dkk (Jurnal Pendidikan Ekonomi, 2018)
The purpose of this study is to determine the effectiveness of training programs and assistance in the preparation of teaching materials for teachers of SMAN 5 Kediri, conducted in April until July 2018. This study used a qualitative approach and type of evaluation research. The instruments of data collection used were interview, observation, document study, and questionnaire. Data analysis using Miles and Huberman (1969). The results showed that overall it can be concluded that the activity of training program and the compilation of teaching materials at SMAN 5 Kediri is effective from 3 measurement variables, namely the participants of training and mentoring; Instructor competence and Scenario training.